Cover Feature: On‐Surface Synthesis and Spectroscopic Characterization of Laterally Extended Chevron Graphene Nanoribbons (ChemPhysChem 18/2019). Issue 18 (12th September 2019) - Teeter, Jacob D.; Zahl, Percy; Mehdi Pour, Mohammad; Costa, Paulo S.; Enders, Axel; Sinitskii, Alexander
Abstract : The Cover Feature illustrates the on‐surface synthesis of graphene nanoribbons on Au(111). The atomically precise structure of the ribbons was confirmed by noncontact atomic force microscopy, while scanning tunneling spectroscopy revealed their bandgap of about 2.2 eV. More information can be found in the Communication by J. D. Teeter et al. on page 2281 in Issue 18, 2019 (DOI: 10.1002/cphc.201900445 ).